A Bayesian Network Model for Predicting Post-stroke Outcomes With Available Risk Factors - Park, Eunjeong; Chang, Hyuk-jae; Nam, Hyo Suk (Frontiers in Neurology, 2018)
Bayesian network is increasingly popular method in modelling uncertain and complex problems, because its interpretability is often more useful than plain prediction. To satisfy the core requirement in medical research to obtain interpretable prediction along with high accuracy, we constructed an inference engine for post-stroke outcomes based on Bayesian network classifiers. The prediction system which was trained on data of 3605 acute stroke patients forecasts the functional independence at 3 months and the mortality one year after stroke. Feature selection methods were applied to eliminate less relevant and redundant features from 76 risk variables. The Bayesian network classifiers were trained with a hill-climbing searching for the qualified network structure and parameters measured by maximum description length. We evaluated and optimized the proposed system to increase the area under the receiver operating characteristic curve (AUC) while ensuring acceptable sensitivity for the class-imbalanced data. The performance evaluation demonstrated that the Bayesian network with selected features by wrapper-type feature selection can predict 3-month functional independence with an AUC of 0.889 using only 19 risk variables and 1-year mortality with an AUC of 0.893 using 24 variables. The Bayesian network with 50 features filtered by information gain can predict 3-month functional independence with an AUC of 0.875 and 1-year mortality with an AUC of 0.895. We also built an online prediction service, Yonsei Stroke Outcome Inference System, to substantialize the proposed solution for stroke patients.